Building partnership in oral cancer research in a developing country: processes and barriers. - Zain, R.; Ghani, W.M.N.; Razak, I.A.; Latifah, R.J.R.; Samsuddin, A.R.; Cheong, S.C.; Abdullah, N.; Ismail, A.R.; Hussaini, H.; Talib, N.A.; Jallaludin, A. (West Asia Organization for Cancer Prevention, 2009)
With the growing partnership, the collaborative group recognizes the need to develop standard operating procedures (SOPs) and guidelines for the sharing and usage of resources in order to safeguard the interest of the original partners while also attending to the needs of the new partners.